Penerapan Clustering Dengan Fuzzy C-Means Dalam Mendiagnosa Radang Asam Urat - Syahrin, Elvin; Juliawan, Dicky (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Inflammation of uric acid is a disease that occurs due to excess uric acid in the blood, which then accumulates and accumulates in the form of crystals in the joints. The high-accuracy uric acid inflammation test must be done several times to treat the inflammation of uric acid in the body. Several indicators in the body can be a starting point for treating gout inflammation. Also, errors, the limitations of medical staff in handling huge amounts of data manually are a problem. One solution for this is to use a computer as a mathematical calculation in the Fuzzy C-Means grouping method. The criteria specified are joint pain, swollen joints, stiff joints, sprained feet and lumps in the joints. The grouping consisted of groups with gout inflammation and non-gout inflammation. Testing was carried out on 14 data.